Complete Denture Fabrication Using Digitally Fabricated Copy Dentures for a Patient with Moderate Dementia - Korehide Arai; Yuto Tanaka; Shinsuke Matsuda; Tomohiko Okamura; Kazufumi Iwayama; Yoshiaki Ono (Hindawi Limited, 2021)
A 91-year-old woman was referred to our hospital with a chief complaint of unsatisfactory fit and pain associated with her complete dentures. She had moderate dementia with difficulty in communication (Mini-Mental State Examination, 16; Barthel Index, 15). The closed impressions and jaw record were taken with the digitally fabricated copy dentures as follows. First, the tissue conditioner was used to correct the poor fit of the old dentures, following which minor occlusal alterations were made. Second, the copy dentures that copied the morphology of the corrected old dentures using three-dimensional (3D) scanner were fabricated with a 3D printer. The new dentures were then fabricated using conventional methods as follows. The impressions were cast and articulated, and the dentures were subsequently processed. This case report documented the following results. First, the acceptance of new dentures appeared to be easier since the new dentures copied the morphology of the familiar dentures digitally. Moreover, the 3D data of the dentures could be used for immediate denture fabrication in case of fracture or loss of the dentures. Second, only two visits were required for taking an impression and delivering the complete dentures. In addition, her old dentures were brought to our dental office by the patient's family after the patient's dinner; immediately after copying the dentures' morphology, the dentures were returned to the patient's family, thus avoiding any disturbance to the patient's eating routine. These reduced the burden on the patient and her family.